The Impact of AI in BIM-to-Digital Twins on Facility Management Handover: Bridging the Gap between Construction and Operations through AI-Driven Integration. - Abdullah Saqr (Management Science Research Journal, 2026)
The present paper will consider how Artificial Intelligence (AI) will help in the shift by Building Information Modeling (BIM) to Digital Twins (DTs), specifically in relation to facility management handover. It deals with the main industrial concerns in the fragmentation of data, lack of interoperability, and ineffective regulatory compliance process by using AI-based solutions to enhance data validation, predictive analytics, and real-time synchronization. The data collection was conducted with the help of a qualitative method based on an interpretivist worldview and grounded theory approach, which allowed collecting data through semi-structured interviews with BIM professionals. The findings prove that AI could be effective to increase the accuracy, effectiveness, and quality of BIM-DT handover procedures, which, in its turn, leads to more efficient operations, proactive maintenance of facilities, and sustainable facility management.